THE PREFERENCE CHOICE OF MODE WITH INTERMODALITY STUDY IN PASSENGER MOVEMENT OF BANDUNG-JAKARTA PUBLIC TRANSPORTATION (Case Study: Mode of Train and 'Travel') - DEWI ANGGRAENI (NIM. 25407004), RATNA
Since the opening of Cipularang toll road, the high demand of public transportation between Bandung-Jakarta creates the growth of commuting between the two cities. Study shows that 70-96% of the passengers who use train or 'travel' are regulars. With the growth of this new phenomenon mode using 'travel' to serve these commuters, right at the same time the number of passengers of train connecting these two cities, which were once the most popular choice of transport (between 1995-2005), are becoming lesser. Even with price reduction, it did not have any effects on the number of train passengers for the last 3 years, between 2005-2008. This phenomenon creates the need to do a study of why train commuting is becoming less and less popular as a choice of transport, by understanding individual preference as a decision maker. The purpose of this research is to know the aspects that affect the preference mode of transport between mode of train and 'travel', by looking at the context of intermodality of commuter movement between the two cities and using model stated preference (SP) to understand commuter preferences. From direct answers analysis, their priorities are actually the point of destination and travel time, not the price factor. While the commuter movement intermodality study shows that most commuters going to the point of departure and from point of arrival going to the end destination by using private car and taxi, followed by public transportation. The average cost and time difference between the two modes of transport is Rp 30.000 more expensive using mode of 'travel', but it is 45 minutes faster. The SP model study with designated situation scenario shows that the probability of using mode of 'travel' is bigger than train, for weekdays and weekends, even though during weekends the difference is very small. Take note this analysis shows that comfort factor, travel time accuracy of mode train and travel cost play dominant factors that affect a model. Measured variable contribution analysis at a model does not give a big contribution (average 24%), other variables, travel behavior and the un-measurable differences in optimum utilization of each mode by each individuals have more effects to the preference of choice between using mode of 'travel' or train. The result of this study hopefully can be useful in providing assistance in making rules and regulations in interregional transportation management between Bandung-Jakarta, in anticipation of commuting movement trend between the two cities. By emphasizing on the potential of public transportation passenger intermodality, a regulation can be made or a concept can be created for an operator that integrates all the operational of public transportation modes so that travel efficiency can be achieved. In addition, this system can also become a source of income for all the local towns and district in the route between Bandung-Jakarta.